Pola Patron Klien Petani Cengkeh dan Pedagang Pengumpul di Desa Lalumpe Kecamatan Motoling Kabupaten Minahasa Selatan - Triolius Lai’ Dadi’ Patandean; Maria Heny Pratiknjo; Mahyudin Damis (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2025)
This study aims to analyze the patron-client relationship pattern between clove farmers and collecting traders in the practice of ijon (crop lien) in Lalumpe Village, Motoling Subdistrict, South Minahasa Regency. This research employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews with six informants, and field documentation. Data analysis was conducted inductively through data reduction, data presentation, and conclusion drawing. The findings reveal that ijon practices are not merely economic transactions, but part of a social relationship system grounded in trust, kinship, and reciprocal dependency. Farmers deliberately choose trusted traders, even though the clove price they receive is far below the market rate. Traders act as patrons by providing unsecured loans with flexible repayment. This relationship forms a mutualistic symbiosis, but also creates long-term structural dependency that economically benefits the traders. These practices are not regulated by formal contracts but by social norms, local ethics, and the moral economy system embedded in Tountemboan agrarian communities. This study concludes that ijon should be understood as a manifestation of local economic culture, rather than merely a mechanism of market exploitation.